Ecofriendly Synthesis of Anisotropic Gold Nanoparticles: A Potential Candidate of SERS Studies - Ujjwala Gaware; Vaishali Kamble; Balaprasad Ankamwar (International Journal of Electrochemistry)
Ecofriendly synthesis of nanoparticles has been inspiring to nanotechnologists especially for biomedical applications. Moreover, anisotropic particle synthesis is an attractive option due to decreased symmetry of such particles often leads to new and unusual chemical and physical behaviour. This paper reports a single-step room-temperature synthesis of gold nanotriangles using a cheap bioresource of reducing and stabilizing agent Piper betle leaf extract. On treating aqueous chloroauric acid solution with Piper betle leaf extract, after 12 hr, complete reduction of the chloroaurate ions was observed leading to the formation of flat and single crystalline gold nanotriangles. These gold nanotriangles can be exploited in photonics, optical coating, optoelectronics, magnetism, catalysis, chemical sensing, and so forth, and are a potential candidate of SERS studies.